ANALISIS KESIAPAN PESERTA DIDIK DAN GURU PADA ASESMEN NASIONAL (ASESMEN KOMPETENSI MINIMUM, SURVEY KARAKTER, DAN SURVEY LINGKUNGAN BELAJAR - Deni Ainur Rokhim; Binti Nuriyati Rahayu; Laila Nur Alfiah; Ristiwi Peni; Bambang Wahyudi; Asnan Wahyudi; Sutomo Sutomo; Hayuni Retno Widarti (Universitas Negeri Malang, 2021)
Abstract: This study aims to see and analyze the readiness of teachers and students in the National Assessment. The research was conducted with a survey method through the distribution of google form questionnaires. The data obtained were analyzed using descriptive statistics. The results of the study group of students showed that 46.6% of students understood national assessment and 53.2% of students did not understand well about national assessment. This is due to the fact that the education unit has not yet disseminated the implementation of the national assessment which has three instruments including the Minimum Competency Assessment (AKM), learning surveys and learning environment surveys. The results of the teacher group research stated that 75% of teachers understood national assessment and 25% of teachers did not understand national assessment. A national assessment is carried out to evaluate the input, process, and quality of teaching and learning in the classroom so as to improve the quality of Indonesian education. Keywords: analysis of the readiness of teachers; students; national assessment Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis kesiapan guru dan peserta didik dalam Asesmen Nasional. Penelitian dilakukan dengan metode survei melalui penyebaran angket google form. Data yang diperoleh dianalisis menggunakan statistik deskriptif. Hasil penelitian kelompok peserta didik menujukkan bahwa 46,6% peserta didik memahami mengenai asesmen nasional dan 53,2% peserta didik belum memahami dengan baik mengenai asesmen nasional. Hal ini disebabkan karena satuan pendidikan terkait belum melakukan sosialisasi penerapan asesmen nasional yang memiliki tiga instrumen penilaian meliputi Asesmen Kompetensi Minimum (AKM), survey belajar, dan survey lingkungan belajar. Hasil penelitian kelompok guru menyatakan bahwa 75% guru memahami mengenai asesmen nasional dan 25% guru belum memahami mengenai asesmen nasional. Asesmen nasional dilakukan untuk melakukan evaluasi terhadap input, proses, dan kualitas belajar-mengajar di kelas sehingga meningkatkan mutu pendidikan Indonesia. Kata kunci: analisis kesiapan guru; peserta didik; asesmen nasional